Inhibition of Propionibacterium acnes lipase activity by the antifungal agent ketoconazole. (14th February 2017) - Unno, Mizuki; Cho, Otomi; Sugita, Takashi
ABSTRACT: The common skin disease acne vulgaris is caused by Propionibacterium acnes . A lipase secreted by this microorganism metabolizes sebum and the resulting metabolites evoke inflammation in human skin. The antifungal drug ketoconazole inhibits P. acnes lipase activity. We previously showed that the drug also inhibits the growth of P. acnes . Thus, ketoconazole may serve as an alternative treatment for acne vulgaris, which is important because the number of antibiotic‐resistant P. acnes strains has been increasing.